AQP4-independent TRPV4 modulation of plasma membrane water permeability - Barile, Barbara; Mola, Maria Grazia; Formaggio, Francesco; Saracino, Emanuela; Cibelli, Antonio; Gargano, Concetta Domenica; Mogni, Guido; Frigeri, Antonio; Caprini, Marco; Benfenati, Valentina; Nicchia, Grazia Paola (Frontiers in Cellular Neuroscience, 2023)
Despite the role of aquaporin (AQP) water channels in controlling transmembrane water fluxes, alternative ways for modulating water permeation have been proposed. In the Central Nervous System (CNS), Aquaporin-4 (AQP4) is reported to be functionally coupled with the calcium-channel Transient-Receptor Potential Vanilloid member-4 (TRPV4), which is controversially involved in cell volume regulation mechanisms and water transport dynamics. Fluorescence-quenching water transport experiments in Aqp4 -/-astrocytes revealed that cell swelling rate is significantly increased upon TRPV4 activation and in the absence of AQP4. The biophysical properties of TRPV4-dependent water transport were therefore assessed using the HEK-293 cell model. Calcein quenching experiments showed chemical and thermal activation of TRPV4 overexpressed in HEK-293 cells leads to faster-swelling kinetics. Stopped-flow light scattering water transport assay was used to measure the osmotic permeability coefficient (Pf, cm/sec) and activation energy (Ea, kcal/mol) conferred by TRPV4. Results provided evidence that although the Pf measured upon TRPV4 activation is lower than the one obtained in AQP4-overexpressing cells (Pf of AQP4= 0.01667 ± 0.0007; Pf of TRPV4= 0.002261 ± 0.0004; Pf of TRPV4+4αPDD= 0.007985 ± 0.0006; Pf of WT= 0.002249 ± 0.0002), along with activation energy values (Ea of AQP4 = 0.86 ± 2 0.0006; Ea of TRPV4+4αPDD= 2.73 ± 1.9; Ea of WT = 8.532 ± 0.4), these parameters were compatible with a facilitated pathway for water movement rather than simple diffusion. The possibility to tune plasma membrane water permeability more finely through TRPV4 might represent a protective mechanism in cells constantly facing severe osmotic challenges to avoid the potential deleterious effects of the rapid cell swelling occurring via AQP channels. Animals. WT and Aqp4 -/-pups with a CD1 genetic background (Basco et al., 2013) were used for dissection in primary astrocyte cultures preparation. All the procedures involving animals were performed accordingly to the European and Italian laws on animal use for research and animal care. This project has been approved by the Italian Health Department (Approved Project no. n°710/2017-PR). Mice were bred in the approved facility at the University of Bari under a 12-hour dark-to-light cycle at constant room temperature (23-25°C) and humidity (22°C±2°C, 75%). The design of